2002
DOI: 10.1103/physrevlett.89.137401
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Electronic Energy Transfer from Excitons Confined in Silicon Nanocrystals to Oxygen Molecules

Abstract: We demonstrate efficient resonant energy transfer from excitons confined in silicon nanocrystals to molecular oxygen (MO). Quenching of photoluminescence (PL) of silicon nanocrystals by MO physisorbed on their surface is found to be most efficient when the energy of excitons coincides with triplet-singlet splitting energy of oxygen molecules. The dependence of PL quenching efficiency on nanocrystal surface termination is consistent with short-range resonant electron exchange mechanism of energy transfer. A hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
92
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(96 citation statements)
references
References 8 publications
0
92
0
4
Order By: Relevance
“…An important property of micro-PS lies in the fact that upon photoexcitation of silicon nancrystals excitons are generated at rather high concentrations (the quantum yield of exciton photoluminescence reaches a few percent (Bisi et al, 2000)). It has been demonstrated that the energy can be effectively transferred from excitons to 3 O 2 molecules adsorbed on the surface of silicon nanocrystals with the subsequent transformation of these molecules into an excited state (Gross et al, 2003;Kovalev et al, 2002). Therein lies the essence of the mechanism of photosensitization of molecular oxygen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important property of micro-PS lies in the fact that upon photoexcitation of silicon nancrystals excitons are generated at rather high concentrations (the quantum yield of exciton photoluminescence reaches a few percent (Bisi et al, 2000)). It has been demonstrated that the energy can be effectively transferred from excitons to 3 O 2 molecules adsorbed on the surface of silicon nanocrystals with the subsequent transformation of these molecules into an excited state (Gross et al, 2003;Kovalev et al, 2002). Therein lies the essence of the mechanism of photosensitization of molecular oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been revealed that photoexcitation of nanocrystals in microporous silicon (micro-PS) layers leads to the generation of singlet oxygen on the surface of the samples (Kovalev et al, 2002). It is known that the ground state of the oxygen molecule is represented by the triplet state ( 3 O 2 , where the superscript indicates the spin multiplicity; the total spin of the triplet molecule is S TO = 1).…”
Section: Introductionmentioning
confidence: 99%
“…Получено аналитическое выражение и дана численная оценка вероятности переноса энергии от нанопористого кремния к молекуле кислорода. Показано, что ее численное значение порядка 10 Недавние исследования показали перспективность нанопористого кремния (np-Si) для задач микро-и оптоэлектроники [1], а также для задач биологии и медицины [2,3]. Как следует из ряда работ [2,4,5], в присутствии возбужденного нанопористого кремния возможна генера-ция синглетного кислорода.…”
unclassified
“…Показано, что ее численное значение порядка 10 Недавние исследования показали перспективность нанопористого кремния (np-Si) для задач микро-и оптоэлектроники [1], а также для задач биологии и медицины [2,3]. Как следует из ряда работ [2,4,5], в присутствии возбужденного нанопористого кремния возможна генера-ция синглетного кислорода. Это было показано как с помощью прямого измерения люминесценции [4], так и косвенно (на основе биологическо-го действия синглетного кислорода) [5].…”
unclassified
“…Then, it is difficult to realize the light emitting devices based on the Si nanocrystal assemblies. It is demonstrated that Si nanocrystals used as efficient photosensitizer for rare earth ions (5)- (6), molecular oxygen (7). Particularly, in the photosensitized effect for the molecular oxygen, the long lifetime of Si nanocrystals is an important role since the decay time of excitons is smaller than the transfer time of electronic excitation energy to molecular oxygen.…”
Section: Introductionmentioning
confidence: 99%